PENINGKATAN KOMPETENSI GURU PAUD DALAM MELAKSANAKAN PEMBELAJARAN BERBASIS KONSEP MERDEKA BERMAIN DI KECAMATAN MARO SEBO ULU KABUPATEN BATANGHARI - Herwina Dewi Librianty; Yennizar; Novi Susanti; Hikmah. M (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2021)
The concept of 'Merdeka bermain' has revolutionized the role of educators, shifting them from the traditional center of learning to facilitators of play-based learning. It emphasizes the pivotal role of play environments in nurturing children's curiosity and engagement. In this framework, preschool (PAUD) teachers function primarily as motivators and facilitators, creating rich and enticing play environments that encourage exploration. To enhance PAUD teachers' competency in 'merdeka bermain,' a service initiative was initiated. It aimed at achieving three key objectives: 1) Enhancing PAUD teachers' comprehension of 'merdeka bermain' and the eight essential indicators in early childhood education. 2) Developing their capacity as motivators and facilitators in the learning process. 3) Strengthening their ability to implement free play-based learning by harnessing local resources. The service activities employed training, technical guidance, and mentoring. Outcomes included improved understanding of 'merdeka bermain,' enhanced motivational and facilitation skills, and a better grasp of incorporating local resources into play-based learning. Constraints included time and funding limitations. Future efforts aim to provide further support to PAUD teachers in Maro Sebo Ulu Sub-district, promoting comprehensive implementation of the eight key indicators, creative game design, optimal utilization of the environment as a learning resource, and precision in assessment.